1994
DOI: 10.1093/geronj/49.3.m133
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Motor Slowness: Simply Strategic?

Abstract: The results suggest a decline in motor coordination rather than any simple strategic preference for caution in movement. The hesitancy of movement to some extent parallels that seen in Parkinson's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
68
0
3

Year Published

1998
1998
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 135 publications
(77 citation statements)
references
References 19 publications
6
68
0
3
Order By: Relevance
“…These results of declining movement parameters with age are similar to those found earlier by others (Morgan et al, 1994;Bennett and Castiello, 1994;Pohl et al, 1996;Welford, 1988). Specifically, the elderly performances were slower than those of young participants as signified by lower peak velocities.…”
Section: Movement Strategysupporting
confidence: 91%
See 1 more Smart Citation
“…These results of declining movement parameters with age are similar to those found earlier by others (Morgan et al, 1994;Bennett and Castiello, 1994;Pohl et al, 1996;Welford, 1988). Specifically, the elderly performances were slower than those of young participants as signified by lower peak velocities.…”
Section: Movement Strategysupporting
confidence: 91%
“…The principal cause of slowing down in the motor behaviour of aged individuals was attributed to the decline in sensorimotor processing in this age group as evidenced by slower movement time (Warabi et al, 1986, Morgan et al, 1994Pohl et al, 1996) or reaction time (Welford, 1988;Bennett and Castiello,1994) in performing discrete tasks. For example, Pohl and colleagues (1996) analysed target approach phase during performance of a reciprocal tapping task to random targets in a group of elderly participants.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Previous studies have reported larger numbers of submovements associated with cursor movements during human-computer interaction (Maraj et al, 1998). In this study there were 2.87 submovements per trial on average, compared with 1.05 submovements when people used a stylus to move 125 mm to targets of 5, 10, or 20 mm diameter on a graphics tablet (Morgan et al, 1994). Nevertheless, there was little evidence that cursor orientation affected submovements, because there were no effects of manipulations on the number of submovements.…”
Section: Kinematic Analysismentioning
confidence: 46%
“…The fact that older adults have had decades of practice with the preferred hand might suggest that older adults should exhibit large motor asymmetries, perhaps even to a greater extent than when young. Aging is, however, associated with changes in motor ability whereby movements become slower and less accurate over time (Desrosiers, Herbert, Bravo and Dutil 1995;Verkerk, Schouten and Oosterhuis 1990;Morgan, Phillips and Bradshaw et al 1994;Pohl, Winstein and Fisher 1995;Welsh, Higgins and Ketcham et al 2002). It is unclear whether this decline in motor ability alters the propensity toward motor asymmetries seen in younger adulthood.…”
Section: Introductionmentioning
confidence: 99%